2018
DOI: 10.1159/000491975
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying H2O2-Evoked Carbonyl Modification of Cytoskeletal Protein and Axon Injury in PC-12 Cells

Abstract: Background/Aims: To investigate the mechanism that enables oxidative stress and cytoskeleton protein carbonylation to contribute to axonal dysfunction in traumatic brain injury (TBI). Methods: We created an in vitro model of neuronal oxidative damage by exposing a neuron-like cell line (PC-12) to different concentrations (100 μM, 200 μM, and 300 μM) of H2O2 for 24 h or 48 h. Carbonyl modification of cytoskeletal proteins (β-actin and β-tubulin) and its impact on β-actin/β-tubulin filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moreover, it has been reported that other factors, such as the depolymerization of cytoskeletal systems, may lead to impaired mitochondrial transportation. In this context, Zhang et al, 2018, demonstrated a H 2 O 2 -induced depolymerization of ß-actin filaments in neuronal cell lines incubated for 24 h with 200 µM H 2 O 2 [44]. Such an effect is, however, very improbable in our experimental brain slices, which were incubated for only 30 min with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, it has been reported that other factors, such as the depolymerization of cytoskeletal systems, may lead to impaired mitochondrial transportation. In this context, Zhang et al, 2018, demonstrated a H 2 O 2 -induced depolymerization of ß-actin filaments in neuronal cell lines incubated for 24 h with 200 µM H 2 O 2 [44]. Such an effect is, however, very improbable in our experimental brain slices, which were incubated for only 30 min with H 2 O 2 .…”
Section: Discussionmentioning
confidence: 68%
“…Beside preventing carbonylation and other oxidative damage of proteins, carnosine may also inhibit cross-linking by reacting with carbonylated proteins (54). Carbonylation of tubulin can impair its polymerization and favor depolymerization of microtubules (55,56). Thus, it is possible that the increase of protein carbonylation in Carns1(-/-) mice may impair the functional properties of ORN axons in the OB, though further studies are necessary to solve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated the role and the potential therapy of activation of RAS or RAP1 in traumatic brain injury [55][56][57]. There were also several studies about the actin cytoskeleton, which showed the mechanism in TBI procedure [58,59]. As the upstream pathway, MAPK signaling pathway may serve as another important role.…”
Section: Discussionmentioning
confidence: 99%